Medicaid beneficiaries undergoing complex surgery at quality care centers: insights into the Affordable Care Act - Hall, Erin C. (Am J Surg, 2016)
BACKGROUND: Medicaid beneficiaries do not have equal access to high-volume centers for complex surgical procedures. We hypothesize there is a large Medicaid Gap between those receiving emergency general vs complex surgery at the same hospital. METHODS: Using the Nationwide Inpatient Sample, 1998 to 2010, we identified high-volume pancreatectomy hospitals. We then compared the percentage of Medicaid patients receiving appendectomies vs pancreatectomies at these hospitals. Hospital characteristics associated with increased Medicaid Gap were evaluated using generalized estimating equation models. RESULTS: A total of 602 hospital-years of data from 289 high-volume pancreatectomy hospitals were included. Median percentages of Medicaid appendectomies and pancreatectomies were 12.1% (interquartile range: 5.8% to 19.8%) and 6.7% (interquartile range: 0% to 15.4%), respectively. Hospitals that performed greater than or equal to 40 pancreatic resections per year had higher odds of having significant Medicaid Gap (odds ratio 2.3, 95% confidence interval 1.1 to 5.0). CONCLUSIONS: Gaps exist between the percentages of Medicaid patients receiving emergency general surgery vs more complex surgical care at the same hospital and may be exaggerated in hospitals with very high volume of complex elective surgeries.